EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK WDEP UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA SMA TINGKAT XI - Zahra, ZahraFaizaArief; Firmansyah, Dida; Irmayanti, Rima (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
Low motivation to learn is still a problem for students at school. One of them is at a high school level. This certainly requires efforts to ensure that it doesn't continue to happen, considering that motivation is something that is very important for students to achieve their goals of success. The aim of this research is to increase students' learning motivation and to measure the effectiveness of group guidance using the WDEP technique. This research took a population of Level The research approach used in this research is quantitative. The effectiveness results of the N-gain pretest and posttest of student learning motivation in the control class were 0.1 in the low category and the experimental class was 1.2 in the high category, the results of the independent t-test were at sig. (2-tailed) is 0.00 < 0.05, which means that the learning motivation of experimental class students is better than the control class. Based on the research results, it shows that the WDEP technique is effective in increasing the learning motivation of Level XI high school students.